Hambatan Penggunaan Aplikasi MyKoPay dalam Mendukung Transformasi Smart City di Kota Payakumbuh - Miftahul Hasnah; Syamsir Syamsir (Lembaga Yasin AlSys, 2025)
The advancement of digital technology has prompted local governments to deliver public services through adaptive and effective electronic platforms. One concrete implementation in Payakumbuh City is the MyKopay application, designed as an integrated platform for various public services in support of the city’s smart transformation initiative. However, the functional realization of this application remains suboptimal. This study aims to examine the barriers to the implementation of the MyKopay application as part of the smart city transformation in Payakumbuh. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and documentation, and analyzed using the Technology Acceptance Model 3 (TAM 3) framework. The findings reveal several obstacles, including weak coordination among local government agencies (OPDs), limited technical human resources, low levels of digital literacy among the public, the absence of technical regulations, and insufficient public outreach. These factors contribute to the low adoption and utilization of the application. The study concludes that institutional strengthening, human resource capacity building, the development of supporting regulations, and effective communication and education strategies are essential to ensure that digital applications serve as practical solutions for public service delivery rather than mere symbols of modernization.